Tracheal intubation with the rigid tube for laryngoscopy – a new method [Retraction] - Marchis IF; Radeanu D; Cosgarea M (Dove Medical Press, 2019)
Marchis IF, Radeanu D, Cosgarea M. Ther Clin Risk Manage. 2019;15:309–313.The Editor-in-Chief and Publisher of Therapeutics and Clinical Risk Management wish to retract the published article.Concerns were raised to the Editor-in-Chief regarding the level of similarity between the published article and another article titled The Rigid Tube of Laryngoscopy – a New Intubation Technique by the same authors in the Proceedings of National ENT, Head and Neck Surgery Conference (17–20 May 2017, Sibiu, Romania).Following an investigation, it was found the level of similarity between the two articles was unacceptable and the authors had failed to notify Therapeutics and Clinical Risk Management of the previous publication. It was determined by the Editor-in-Chief the authors had not modified the article submitted to Therapeutics and Clinical Risk Management sufficiently enough for it to be considered new information and it was found to be aredundant publication.This retraction relates to this paper